Visualising residents' fear of crime with recorded crime data from four Czech cities. Issue 1 (1st January 2022) - Linhartová, Petra; Ivan, Igor; Pánek, Jiří
ABSTRACT: The paper investigates if and where registered crime and the fear of crime intersect in the four locations. This information is important to reduce crime and increase the sense of security of the population. In the past, research was applied to small parts of a city or a whole city, but not in as much detail as this paper. Our research is detailed, and at the same time is applied to four entire locations - three Czech cities (Ostrava, Olomouc, and Kolín) and one Prague district (Prague 12). We placed registered crime and fear of crime on one map to show locations where people feel afraid, where crime happens, and where both events occur together. We drew these phenomena using Moran's I in a bivariate map. The outputs will be applied by Municipal governments and police departments.